Human Galectin-7 Gene LGALS7 Promoter Sequence Polymorphisms and Risk of Spontaneous Intracerebral Hemorrhage: A Prospective Study - Wang, Ming-Dong; Tian, Jing; Zhang, John H.; Zhao, Shun-Ying; Song, Ming-Jing; Wang, Zhan-Xiang (Frontiers in Molecular Neuroscience, 2022)
BACKGROUND AND PURPOSE: Despite evidence of genetic role in stroke. A small proportion of stroke are attributable to monogenic condition, however stroke syndrome becomes more complicated by phenotype heterogeneity. The goal of this study is to sought to examine the relationship between the polymorphisms of the galectin-7gene promoter region and intracerebral hemorrhage. METHODS: we conducted a two stages (exploratory and discovery) genetic association study. By constructing Transgenic mice; identified the gene, differential proteins and associated proteins of galectin-7, and applied a single-nucleotide-polymorphism (SNP) genotyping approach to 24 individuals of Chinese ancestry with hemorrhagic stroke and finally, the relationships of 2 SNPs of the LGALS 7 gene with intracerebral hemorrhage were investigated in this Chinese cohort. RESULTS: the exploratory phase, relative to TGLGALS mice, the LGALS 7 exhibited decreases in TGLGALS-DOWN mice. The discovery phase included 24 ICH cases and identified 2 susceptibility loci: a genomic region on 19q13.2(rs567785577, rs138945880). the rs567785577 and rs138945880 SNP (A allele, T allele) of Galectin-7 was associated with cerebral hemorrhage (for T, versus A, unadjusted odds ratio [OR]=13.5; 95%confidence interval [CI]=2.249 to 146.5; P=0.002). This is the first study to genotyping Galectin-7 in patients with hemorrhagic stroke. Genotype and allele association tests and preliminary analysis of stroke patients revealed that a single locus may be a genetic risk factor for hemorrhagic stroke. CONCLUSIONS: we identified A allele, T allele of 19q13.2 (rs567785577, rs138945880) as two novel SNP loci susceptibility risk for ICH. Further expansion of case numbers and replication and subsequent translational studies in other ethnic groups are needed to elucidate the mechanisms underlying this associations in mediating intracerebral hemorrhage.